2010
DOI: 10.1016/j.neuron.2009.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic and Network Mechanisms of Sparse and Reliable Visual Cortical Activity during Nonclassical Receptive Field Stimulation

Abstract: SUMMARY During natural vision, the entire visual field is stimulated by images rich in spatiotemporal structure. Although many visual system studies restrict stimuli to the classical receptive field (CRF), it is known that costimulation of the CRF and the surrounding nonclassical receptive field (nCRF) increases neuronal response sparseness. The cellular and network mechanisms underlying increased response sparseness remain largely unexplored. Here we show that combined CRF + nCRF stimulation increases the spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
293
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(327 citation statements)
references
References 94 publications
34
293
0
Order By: Relevance
“…This result is consistent with our present study, as the movies we used spanned a large portion of the visual field. Thus, we believe that the fact that we found lower temporal variability in the movie responses compared with the grating responses can at least in part be explained by the same network effects observed by Haider et al (2010); rich, full-field stimuli engage the cortical network, whereas these effects are much less pronounced when simplistic stimuli are presented. Indeed, previous studies have found that combinations of simple stimuli, such as bars of different orientations, engage the visual cortex differently than if those features were presented in isolation.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This result is consistent with our present study, as the movies we used spanned a large portion of the visual field. Thus, we believe that the fact that we found lower temporal variability in the movie responses compared with the grating responses can at least in part be explained by the same network effects observed by Haider et al (2010); rich, full-field stimuli engage the cortical network, whereas these effects are much less pronounced when simplistic stimuli are presented. Indeed, previous studies have found that combinations of simple stimuli, such as bars of different orientations, engage the visual cortex differently than if those features were presented in isolation.…”
Section: Discussionsupporting
confidence: 56%
“…High reliability in neural responses to natural movie stimuli was recently reported by Haider et al (2010). Interestingly, reliability, as well as sparseness, increased when the nonclassical receptive field was stimulated, compared with when only the classical receptive field received stimulation.…”
Section: Discussionsupporting
confidence: 51%
“…In this context, the activity of inhibitory cells within the visual network depends on stimulus condition and different sizes lead to changes in the excitation to inhibition balance—and weak suppression of interneurons [Haider et al, 2010]. Changes in the amplitude of gamma oscillations may be due to interactions between principal cells and interneurons as the grating patch expands beyond the classical receptive field.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of correlated activity (decorrelation) best accounts for perceptual improvements in these tasks (Cohen and Maunsell, 2009), but the neuronal subtypes involved remain unclear. Identifying cortical neuron subtypes in higher mammals presents challenges, since action potentials of many excitatory neurons are indistinguishable from those of inhibitory neurons (Constantinople et al, 2009;Haider et al, 2010;Soares et al, 2017;Vigneswaran et al, 2011). This may hinder full understanding of excitatory and inhibitory contributions to decorrelation and sensory perception.…”
Section: Introductionmentioning
confidence: 99%